Secondary Cities : Engines of Job Creation in Uganda - Wadie, Emma (World Bank, Washington, DC, 2020)
This policy note focuses on the role of secondary cities as engines of job creation in Uganda and on the key actions and investments that the Government of Uganda (GoU) could take to strengthen this role. The note will examine why secondary cities are important for creation of more and better jobs, where the cities with the most potential are, how Government can contribute, and finally who the actors involved should be.